2009
DOI: 10.1592/phco.29.11.1297
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Outcomes of a Simplified, Weight‐Based, Extended‐Interval Gentamicin Dosing Protocol in Critically Ill Neonates

Abstract: This simplified, weight-based, extended-interval gentamicin dosing protocol for critically ill neonates was effective in achieving therapeutic peak plasma concentrations of gentamicin in most of the patients and, as a high proportion of patients had acceptable trough concentrations, may minimize the potential for toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…Unfortunately, PK data in adult patients on ECMO are sparse. Neonatal and animal studies are available but have shown significant variability and unpredictability of antibiotic PK during ECMO [32,35,46,50,[66][67][68][69][70][71][72][73][74][75][76][77][78][79] (Table 1). However, no dosing guidelines exist for this group of patients.…”
Section: Antibioticsmentioning
confidence: 99%
“…Unfortunately, PK data in adult patients on ECMO are sparse. Neonatal and animal studies are available but have shown significant variability and unpredictability of antibiotic PK during ECMO [32,35,46,50,[66][67][68][69][70][71][72][73][74][75][76][77][78][79] (Table 1). However, no dosing guidelines exist for this group of patients.…”
Section: Antibioticsmentioning
confidence: 99%
“…Drug metabolism is minimal as approximately 99% of the administered AGs are eliminated unaltered by glomerular filtration in the proximal tubule [34, 35]. The plasma half-life of AGs ranges from 1.5 to 3.5 hours [7, 36], but is prolonged in neonates, infants, and conditions with decreased kidney function [7, 37]. …”
Section: Pharmacokinetics and Antimicrobial Mechanism Of Aminoglycmentioning
confidence: 99%
“…The mean gentamicin CL ranged from 0.028 to 0.07 L/hr/kg, the mean half-life ranged from 3.85 to 9.23 hours, and the mean or median central V D ranged from 0.39 to 0.98 L/kg [106108,112]. In comparison, non-critically ill children had a mean CL of 0.042 L/hr/kg, mean half-life ranging from 2–8 hours, and a mean V D ranging from 0.3–0.43 L/kg [113,114].…”
Section: Pharmacokinetic Studies In Critically Ill Childrenmentioning
confidence: 99%